2021
DOI: 10.1302/2058-5241.6.200059
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin presoaking of hamstring autografts to prevent infection in anterior cruciate ligament reconstruction: a narrative review

Abstract: Hamstring autograft use has been linked to an increased risk of infection after anterior cruciate (ACL) reconstruction compared to other grafts. The absolute reason for this remains unclear, with contamination after harvesting and preparation of the graft being the most accepted hypothesis. Using the rationale that a contaminated graft could be the main factor in postoperative septic arthritis and in an effort to maximize the antibiotic efficacy of the graft, the Vancomycin presoaking technique was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…According to Figueroa 39 , the use of HT autografts has been related to an increased risk of infection following ACLR compared to other graft types. The reason for this is not clear, although contamination following harvesting and graft preparation is the most probable cause.…”
Section: Discussion Vancoymicin Wrap: Should It Be the New Gold Standard?mentioning
confidence: 99%
“…According to Figueroa 39 , the use of HT autografts has been related to an increased risk of infection following ACLR compared to other graft types. The reason for this is not clear, although contamination following harvesting and graft preparation is the most probable cause.…”
Section: Discussion Vancoymicin Wrap: Should It Be the New Gold Standard?mentioning
confidence: 99%
“…However, discrepancies among different studies as well as the dearth of prospective randomized control trials make it untimely to advise generalization of this procedure. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Offerhaus et al [21] demonstrated significant reduction in superficial and deep infection using vancomycin pre‐soaked autografts for ACL reconstruction with no compromise in graft quality. Vancomycin is an ideal antibiotic agent due to its pharmacokinetic properties [4, 6, 18]. Vancomycin is a heat stable and water‐soluble antibiotic with a high volume of distribution [4].…”
Section: Discussionmentioning
confidence: 99%
“…Other than providing structure support, allografts can be an effective reservoir for local antibiotic delivery. Within literature, local administration of vancomycin has aided to reduce infection rates and wound complications in spine surgery, ligament reconstruction as well as arthroplasty [4, 6, 18, 21, 22]. During anterior cruciate ligament (ACL) reconstruction, pre‐soaking the grafts in vancomycin solution is a critical step in reducing graft‐related infections [4, 22].…”
Section: Introductionmentioning
confidence: 99%